Effect of Nifedipine Used in the Treatment of the Threat of Preterm Labor on Total Uterine Artery Blood Volume Flow Rate - Eroğlu, Hasan; Turgal, Mert; Altınboğa, Orhan; Karakoç, Gökhan; Sarsmaz, Kemal; Yucel, Aykan (Zeitschrift für Geburtshilfe und Neonatologie, 2023)
Purpose Evaluation of the effect of maternal nifedipine treatment on total uterine artery blood volume flow rate (TVFR).Methods In this prospective study, 43 women who were admitted to the Perinatology Department of the University of Health Sciences Etlik Zübeyde Hanım Gynecology Training and Research Hospital, with the diagnosis of the threat of preterm labor, and 40 healthy pregnant women, who were randomly selected as the control group, were evaluated between July 1, 2018, and September 1, 2018. A transabdominal ultrasound examination of uterine arteries was performed both before and 48 hours after administration of oral nifedipine for TVFR measurement. For the final analysis, the TVFR levels of the group diagnosed with the threat of preterm labor and the control group were compared.Results There was no significant difference in either uterine artery pulsatility index or resistance index values as well as the diameters of the uterine arteries after nifedipine treatment (p>0.05 for all). Total uterine artery blood volume flow rate (TVFR) was 424.66±236.74 mL/min before and 543.39±309.68 mL/min after treatment with nifedipine and was statistically significantly higher (p < 0.05).ConclusionsOur study showed a statistically significant increase in total uterine artery blood volume flow rate 48 hours after oral nifedipine treatment.
Keywords: nifedipine; total uterine artery blood volume flow rate; preterm labor; pulsatility indeks; pulsatility indeks; uterine artery